2014
DOI: 10.1093/mnras/stu515
|View full text |Cite
|
Sign up to set email alerts
|

Kiloparsec-scale outflows are prevalent among luminous AGN: outflows and feedback in the context of the overall AGN population

Abstract: We present integral field unit (IFU) observations covering the [O III]λλ4959, 5007 and Hβ emission lines of sixteen z < 0.2 type 2 active galactic nuclei (AGN). Our targets are selected from a well-constrained parent sample of ≈ 24, 000 AGN so that we can place our observations into the context of the overall AGN population. Our targets are radio-quiet with star formation rates ( [10-100] M ⊙ yr −1 ) that are consistent with normal star-forming galaxies. We decouple the kinematics of galaxy dynamics and merger… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

56
678
11
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 489 publications
(747 citation statements)
references
References 225 publications
(377 reference statements)
56
678
11
2
Order By: Relevance
“…Another peculiarity of FeLoBALs which deserves particular notice is the presence of AGN-driven outflows which, extending up to kpc scale, are thought to have a crucial impact on the host galaxy (de Kool et al 2002;Cicone et al 2014;Harrison et al 2014). In a recent study conducted by Farrah et al (2012) on FeLoBAL QSOs, a clear anticorrelation between the starburst contribution to the IR luminosity and the BI is shown.…”
Section: Discussionmentioning
confidence: 97%
“…Another peculiarity of FeLoBALs which deserves particular notice is the presence of AGN-driven outflows which, extending up to kpc scale, are thought to have a crucial impact on the host galaxy (de Kool et al 2002;Cicone et al 2014;Harrison et al 2014). In a recent study conducted by Farrah et al (2012) on FeLoBAL QSOs, a clear anticorrelation between the starburst contribution to the IR luminosity and the BI is shown.…”
Section: Discussionmentioning
confidence: 97%
“…However, in the absence of a measurement for all the sources, we decided to adopt a value of ne = 100 cm −3 , as routinely adopted in similar studies of the ionized components based on Hβ fluxes (e.g. Liu et al 2013;Harrison et al 2014). This choice is also justified by the slit-resolved spectral analysis of XID5321 presented in Perna et al (2014), where we infer ne = 120 cm −3 from the [SII] ratio at the outflow position and outside the central 1 extraction.…”
Section: Mass Outflows Rates and Energeticmentioning
confidence: 99%
“…Only very recently spatially resolved optical, far infrared and mm spectroscopic studies convincingly showed evidences for the existence of such processes in the form of the predicted energetic outflows in ULIRGs with Seyfert nuclei in the local Universe (e.g. Feruglio et al 2010;Fischer et al 2010;Rupke & Veilleux 2011;Villar-Martín et al 2011;Rodríguez-Zaurín et al 2013;Zhang et al 2011;Westmoquette et al 2012;Rupke & Veilleux 2013;Harrison et al 2014;McElroy et al 2014; see also Elvis 2000 for a discussion on the ubiquitous presence of winds in the AGN structure).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, substantial feedback from accretion around supermassive black holes is required in cosmological semi-analytic models, semi-empirical models, and hydrodynamical simulations to achieve the steep slope of the high-mass end of the galaxy stellar mass function (e.g., Vogelsberger et al 2014a,b;Henriques et al 2015;Schaye et al 2015). Observationally, direct measurements of AGN driven winds in galaxies and radio jet induced bubbles in galaxy haloes have provided evidence for the mechanisms by which AGN feedback can affect galaxies, but typically only for a very small number of galaxies (e.g., McNamara et al 2000;Nulsen et al 2005;McNamara et al 2007;Dunn et al 2010;Fabian 2012;Cicone et al 2013;Liu et al 2013;Harrison et al 2014Harrison et al , 2016. Hence, whether or not AGN feedback actually quenches galaxies in statistically significant numbers remains an open question.…”
Section: Introductionmentioning
confidence: 99%